2022
DOI: 10.1038/s41598-022-11200-0
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of maxillofacial bone defects using patient-specific long-lasting titanium implants

Abstract: The objective of this retrospective study is to verify the effectiveness and safety of patient-specific titanium implants on maxillofacial bones, with a long-term follow-up. Total 16 patients with various maxillofacial defects underwent reconstruction using patient-specific titanium implants. Titanium implants, manufactured by electron beam melting, selective laser sintering, or milling, were inserted into the maxilla, mandible, or zygoma. Long-term follow‐up (36.7 ± 20.1 months) was conducted after the surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 34 publications
0
33
0
3
Order By: Relevance
“…Subsequently, the patient-specific titanium plates utilized to reconstruct maxillofacial bone defects were of great interest. Lim et al (2022) conducted a long-term follow-up of 16 patients who underwent reconstruction using patient-specific titanium plates. Albeit this customized-plates reduced fixation failure and aesthetically unsatisfactory complications, it cannot rehabilitate the masticatory function, which remains a deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the patient-specific titanium plates utilized to reconstruct maxillofacial bone defects were of great interest. Lim et al (2022) conducted a long-term follow-up of 16 patients who underwent reconstruction using patient-specific titanium plates. Albeit this customized-plates reduced fixation failure and aesthetically unsatisfactory complications, it cannot rehabilitate the masticatory function, which remains a deficiency.…”
Section: Discussionmentioning
confidence: 99%
“… 1 9 Reviewing the literature several reports were published on the use of 3D printing techniques to reconstruct the mandible. 6 10 However, few studies were reported on the use of 3D-custom-made implants to reconstruct the maxilla. These mainly focused on the use of 3D subperiosteal implants to reconstruct the atrophic maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than reconstructing large bony defects of the maxilla after ablative tumor surgery. 1 6 Mastication and pronunciation are important functions of the mandible and maxilla that can be restored with dental rehabilitation. The use of 3D-custom-made implants for occlusal rehabilitation is limited in that dental implants cannot be installed into the custom-made implant body itself during the fabrication process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Titanium/Ti6Al4V are involved in bone tissue remodeling, bone defect repair, knee implant, etc. 34,36,37 Gold nanotubes or nanowires can be combined with decellularized extracellular matrix to form hydrogel for tissue engineering 38 or directly used for medical implant 39 .…”
Section: Natural Hydrogelsmentioning
confidence: 99%